CORONARY ANGIOGRAPHY FOLLOWING CARDIAC ARREST WITHOUT ST-SEGMENT ELEVATION: A MULTICENTER STUDY. - Aman Sinha (Student's Journal of Health Research, 2023)
Background:  Ischemic heart disease is a leading reason of cardiac arrest outside the hospital. However, the best approach for treating successfully resuscitated cardiac arrest patients without ST-segment elevation myocardial infarction (STEMI) remains uncertain. Methods:  The primary endpoint of this multicenter study was survival at 90 days; secondary endpoints included duration of catecholamine support, myocardial injury, indicators of shock, length of time on mechanical breathing, ventricular tachycardia recurrence, significant bleeding, need for renal replacement therapy, acute kidney injury, neurologic status at ICU discharge, and time to reach the target temperature. Following neurological recovery, 152 patients who had suffered cardiac arrest but had not had STEMI were randomized to either quick coronary angiography or delayed coronary angiography, with PCI administered as needed. Results:  The immediate angiography category had 63.5% survival at 90 days (56 out of 123 participants), while the delayed angiography category had 66.2% survival (68 out of 95 patients). In the immediate angiography category, the median time to reach the goal temp. was 5.3 hours, while in the delayed angiography category, it took 4.6 hours. The remaining secondary endpoints showed no discernible differences between the categories. Conclusions:  Within the category of patients who underwent successful resuscitation following an out-of-hospital cardiac arrest and did not exhibit indications of STEMI, the overall survival at 90 days did not demonstrate a superiority between an urgent angiography method and a delayed angiography strategy. Recommendation:  Based on the findings of this study, there is no clear superiority between an urgent angiography approach and a delayed angiography strategy for patients who have been successfully resuscitated following an out-of-hospital cardiac arrest without indications of ST-segment elevation myocardial infarction (STEMI). Further research and clinical guidelines may be necessary to determine the most effective treatment approach for this patient population.